Comparison of gut microbiota between immigrant and native populations of the Silver-eared Mesia (Leiothrix argentauris) living in mining area - Zhou, Tianlong; Liu, Shilong; Jiang, Aiwu (Frontiers in Microbiology, 2023)
The complex gut bacterial communities have a major impact on organismal health. However, knowledge of the effects of habitat change on the gut microbiota of wild birds is limited. In this study, we characterized the gut microbiota of two different subspecies of the Silver-eared Mesia (Leiothrix argentauris), the native subspecies (L. a. rubrogularis) and immigrant subspecies (L. a. vernayi), using 16S rRNA gene high-throughput sequencing. These two subspecies live in a trace metal-contaminated area, and L. a. vernayi was trafficked. They are an excellent system for studying how the gut microbiome of wild animal changes when they move to new habitats. We hypothesized that the immigrant subspecies would develop the same adaptations as the native subspecies in response to habitat changes. The results showed that there were no significant differences in the composition, diversity, or functional metabolism of gut microbiota between native and immigrant subspecies under the combined action of similar influencing factors (the p values of all analyses of variance >0.05). In addition, the composition and functional metabolism of gut microbiota in two subspecies showed adaptation against trace metal damage. Linear discriminant analysis effect size (LEfSe) analysis revealed that Massilia in the intestinal microbiota of immigrant subspecies was significantly higher than that of native subspecies, suggesting that immigrant subspecies suffered habitat change. Finally, we found that these two subspecies living in the mining area had an extremely high proportion of pathogenic bacteria in their gut microbiota (about 90%), much higher than in other species (about 50%) living in wild environment. Our results revealed the adaptation of intestinal microbiota of immigrant Silver-eared Mesias under heavy metals stress, which would provide guidance for biodiversity conservation and pollution management in mining area.